2006
DOI: 10.1080/10903120500541050
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Restraint Use, Patient Injury, andAssaults on Ems Personnel

Abstract: Multiple factors are correlated with assaults on EMS personnel by patients requiring restraints. By specifically targeting patients exhibiting these factors, EMS providers can help prevent injury to themselves. Patients not exhibiting these factors may be less dangerous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 26 publications
1
37
0
5
Order By: Relevance
“…In addition to documenting that psychiatric patients may be assaultive [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], this study's findings are consistent with the earlier studies on single precipitants [5,[8][9][10][11][12][13][14][15] and also on multiple precipitants [3,4,6,7,13,14,17,18]. The findings support its hypothesis that the violence triad would be more highly associated with subsequent assaults than single precipitants [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to documenting that psychiatric patients may be assaultive [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], this study's findings are consistent with the earlier studies on single precipitants [5,[8][9][10][11][12][13][14][15] and also on multiple precipitants [3,4,6,7,13,14,17,18]. The findings support its hypothesis that the violence triad would be more highly associated with subsequent assaults than single precipitants [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of single variable prediction has led some investigators to consider possible multiple predictor determinants [3,4,6,7,13,14,17,18]. While some of these researchers have still found one single highly associated predictor from among the multiple variables that they were assessing, such as substance use history in urban youth [3] or intoxication of domestic violence partner [5], other investigators have in fact found multiple determinants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Several factors contribute to patient violence toward EMS personnel; proper measures taken to prevent and reduce patient violence may decrease WRIs. [11] News portraying EMS personnel in an unfavorable light is prevalent in the Turkish media, [12] and there can be no doubt that this increases the rate of violence, causing health service personnel additional, unnecessary stress.…”
Section: Discussionmentioning
confidence: 99%
“…12 Η απουσία σαφών οδηγιών έχει ως συνέπεια τα ανεπιθύμητα συμβάντα, κατά τη διάρκεια των περιοριστικών τεχνικών να είναι σχετι-κά συχνά, ενώ σε κάποιες περιπτώσεις έχουν ως συ-νέπεια τον θάνατο των περιορισμένων ασθενών. [13][14][15] Σε κάθε περίπτωση οι περιοριστικές μέθοδοι απο-τελούν τραυματική εμπειρία τόσο για τους ασθενείς όσο και για τα εμπλεκόμενα μέλη του προσωπικού, ενώ παράλληλα η εκπαίδευση του προσωπικού σε τε-χνικές αποκλιμάκωσης και διαχείρισης της διέγερσης είναι εξαιρετικά περιορισμένες. 16 Οι ψυχολογικές συ-νέπειες των περιοριστικών μέτρων και η ανάπτυξη με-θόδων περιορισμού της χρήσης τους, έχουν ευρύτατα μελετηθεί σε πολλές προηγούμενες δημοσιεύσεις.…”
Section: συζήτησηunclassified